2020
DOI: 10.1002/leap.1299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of untrustworthy journals: Transition from formal criteria to a complex view

Abstract: Not all the journals included in credible indices meet the ethical rules of COPE, DOAJ, OASPA, and WAME, and there may also be trustworthy journals excluded from these indices, which means they cannot be used as whitelists for trustworthy journals. Equally, the many methods suggested to determine trustworthiness are not reliable because they include questionable criteria. The question arises whether valid criteria for identifying an untrustworthy journal can be determined and whether other assessment procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Identifying the predatory publication outlets can be very difficult and existing frameworks struggle as they typically include problematic control criteria (Kratochvíl et al, 2020). A wide variety of degrees, types, and combinations of illegitimate behaviour (Siler, 2020) exists.…”
Section: Identifying Predatory Journalsmentioning
confidence: 99%
“…Identifying the predatory publication outlets can be very difficult and existing frameworks struggle as they typically include problematic control criteria (Kratochvíl et al, 2020). A wide variety of degrees, types, and combinations of illegitimate behaviour (Siler, 2020) exists.…”
Section: Identifying Predatory Journalsmentioning
confidence: 99%
“…The downstream impacts of poorly developed policies, when implemented at a national scale, may hurt many academics by providing poor advice, e.g., in India (Patwardhan et al, 2018 ). When such variable, fluctuating, and to some extent unreliable (Kratochvil et al, 2020 ) lists or criteria are used to classify academics or academic institutions, there is the risk or misclassification (e.g., calling a surgery journal that may be blacklisted as a “predatory surgery journal”) (Teixeira da Silva, 2021b ), which may cause inaccurate and unfair reputational damage through false accusations or unsubstantiated mischaracterizations (Tsigaris & Teixeira da Silva, 2019 , 2020 ). Moreover, such issues and limitations are not limited to open access (Olivarez et al, 2018 ).…”
Section: Why Does An Indistinct Zone Of Predatory Publishing Exist?mentioning
confidence: 99%
“…For this reason, Kratochvíl et al ( 2020 ) proposed to move from a simple set of formal criteria to a complex view of scholarly publishing. After assessing different lists of criteria taken from Beall, COPE, DOAJ, OASPA, and WAME, they revealed that 28% of the journals which were evaluated had been incorrectly assessed as untrustworthy.…”
Section: What Criteria For Predatory Publishing Have Been Proposed To Date?mentioning
confidence: 99%
“…The quality of any academic journal is dependent on its editorial process, the people involved, its originality, management of ethics issues, conflict of interest and peer-review process (Jefferson et al, 2002;Kratochvíl et al, 2020). Based on this, ERRCDF, through IJSS, has adopted a rigorous and academic tasking editorial process discussed below.…”
Section: Ijss Editorial Guidelines and Processmentioning
confidence: 99%